China, space weapons, and U.S. security - MacDonald, Bruce W. (Council special report, 2008)
With China's successful test of an anti-satellite (ASAT) system in 2007, space may well become a new realm for combat as well as for commerce. An offense-oriented space world will have major implications for U.S. force posture, international relations, and the reactions of America and China to perceived threats from other countries. Bruce W. MacDonald recommends options and policies that will promote American security interests in space. He argues that the United States needs to take priority defensive military space measures to offset potential Chinese anti-satellite and related capabilities. Furthermore, the United States needs to initiate discussions with China on space "rules of the road," "incidents in space," and other confidence-building measures. MacDonald also assesses the implications and consequences for U.S. security of an offense-dominant space environment and identifies the kinds of offensive and other capabilities the United States would need to maintain its security in such an environment. Last, he recommends a thorough interagency review of possible bilateral and multilateral restrictions protecting space assets that would enhance U.S. security interests.